“#WalangPasok”: The Use of Twitter During Pre-Typhoon as the Source of Information for Class Suspension among the College Students Studying in Makati City - Villamor, Lyka Beatrice C. (Animo Repository, 2023)
The day-to-day usage of social media such as Twitter during disasters allows everybody involved when it comes to sharing, reporting, and covering news and events. In unpredicted circumstances during disasters, being oblivious to knowing whom and which information is deemed trustworthy has brought up an issue of fallacies and information overload. Our study focuses on the use of Twitter as a platform for information dissemination about class suspensions with typhoons and other disasters for college students in Makati City. Results suggest that the majority of the population uses Twitter as a source of information for class suspension and disaster-related news. The Philippine Atmospheric Geophysical and Astronomical Services Administration ranked first among the Twitter accounts followed by the students during a natural calamity. Additional findings suggest that most of the college students from Makati City believe the veracity of a tweet if it came from a verified account. Lastly, most of the college students feel neutral on the accuracy of the tweets even if a tweet garnered a thousand likes, contains data and statistical information, or if the announcement claims that it came from the local government unit.